Implementasi sertifikasi guru dalam membangun lembaga pendidikan Islam - Al-Khatib, Ibadurrahman (Tawazun: Jurnal Pendidikan Islam, 2022)
Education is an important aspect of life. All the things that everyone does in their lives are part of the process and also the product of education. Including building and advancing the standard of life of the Indonesian nation is with the educational path. However, the results of the 2018 Programme for International Student Assessment (PISA) study reported that out of 399 education units with 12,988 participants, Indonesia is still included in the low-performance category, which means that the condition of education in Indonesia, in general, has not reached its maximum (low) condition. This indicates that the role of educational institutions in Indonesia still needs to be improved, especially in the assessment indicators of educational institutions. One of the ways taken by the government is by certified teachers. This study tries to find out how the implementation of teacher certification in building the protection of educational institutions. This research uses a qualitative approach with a case study approach at SMAIT Ummul Quro. The results of the study prove that teacher certification builds the protection of educational institutions through improving teacher professionalism, teacher discipline, learning innovation, community interest, and the quality of school achievement. Abstrak Pendidikan adalah aspek penting dalam kehidupan. Semua hal yang dikerjakan setiap orang dalam kehidupannya adalah bagian dari proses dan juga produk pendidikan. Termasuk untuk membangun dan memajukan taraf kehidupan bangsa Indonesia adalah dengan jalur pendidikan. Akan tetapi, hasil studi Programme for International Student Assessment (PISA) 2018 melaporkan bahwa dari 399 satuan pendidikan dengan 12.988 peserta, Indonesia masih masuk ke dalam kategori low performance, yang berarti kondisi pendidikan di Indonesia secara umum belum mencapai kondisi maksimal (rendah). Hal ini menandakan peranan lembaga pendidikan di Indonesia masih perlu ditingkatkan, terutama dalam indikator penilaian lembaga pendidikan. Salah satu cara yang ditempuh oleh pemerintah adalah dengan sertifikasi guru. Penelitian ini mencoba untuk mengetahui bagaimana implementasi dari sertifikasi guru dalam membangun perlindungan lembaga pendidikan. Penelitian ini menggunakan pendekatan kualitatif dengan pendekatan studi kasus di SMAIT Ummul Quro. Hasil penelitian membuktikan bahwa sertifikasi guru membangun perlindungan lembaga pendidikan melalui peningkatan profesionalisme guru, kedisiplinan guru, inovasi pembelajaran, minat masyarakat dan mutu prestasi sekolah.